Exploring the Link between Anisometropia, Binocular Vision Depth Perception, and Amblyopia in School-Aged Children: Insights from a Quantitative Study - Yulianti Kuswandari (Formosa Journal of Science and Technology, 2023)
The study examined the relationship between anisometropia degree, binocular vision depth perception, and amblyopia in school-aged children. The research utilized a descriptive quantitative design at Dr. Soetomo Hospital Surabaya from November 2021 to January 2023. The findings indicated a correlation between anisometropia degree and binocular vision depth perception. As the refraction difference increased, the ability to perceive objects with three-dimensional vision diminished. However, no definitive correlation was found between anisometropia degree and amblyopia. To further explore these relationships, future research could involve a broader population, consider additional factors, employ more in-depth study designs, and expand the duration of the study. A more comprehensive understanding of anisometropia, binocular vision depth perception, and amblyopia in children can be attained by addressing these recommendations.